Product property on generalized Lindelof spaces. - Kilicman, Adem; Fawakhreh, Anwar Jabor (Hindawi Publishing Corporation, 2011)
We study the product properties of nearly Lindelof, almost Lindelof, and weakly Lindelof spaces. We prove that inweak P-spaces, these topological properties are preserved under finite topological products.We also show that the product of separable spaces is weakly Lindelof.